DISP-14. DEFINING INTERVENTIONS AND METRICS TO IMPROVE DIVERSITY IN CNS CLINICAL TRIAL PARTICIPATION: A SNO AND RANO EFFORT. (14th November 2022) - Budhu, Joshua; Porter, Alyx; Jackson, Sadhana; Lee, Eudocia; McFaline-Figueroa, J Ricardo; Willmarth, Nicole; Dalmage, Mahalia; Kawachi, Ichiro; Arons, David; Chang, Susan M; Wen, Patrick Y; Hervey-Jumper, Shawn L; et al.
Abstract: Despite major strides in cancer research, care, and therapy, these advances have not been equitable across race and ethnicity. Groups underrepresented in medicine (URM) are more likely to have inadequate preventive screening, increased delays in diagnosis, and poor representation in clinical trials. Notably, Black and Latino Americans represent 29% of the population but only reflect 8% of oncology clinical trial participants. Recent studies have shown that this disparity is also present in neuro-oncology as women, Black, and Latino Americans remain under-accrued in clinical trials. Brain tumor patients already face unique barriers to clinical trial enrollment and completion due to disease-specific conditions–such as impaired motor function, cognition, language deficits, and caregiver dependency–which pose additional difficulties in clinical trial consent, enrollment, and adherence. As part of this collaborative initiative, we evaluated the impact of how a lack of diversity in cancer research is detrimental to scientific discovery and propose interventions focused on improving URM engagement with clinical research. Recommendations include the creation of inclusive trial design at the onset, decreasing barriers to care, expanding trial eligibility, and equitable access to tumor profiling for personalized medical trials. Additionally, setting reasonable metrics and goals for accrual and engagement with patient and community stakeholders will ultimately help to diversify trial participants. Lastly, diversification and inclusion practices within the neuro-oncology workforce, including all personnel involved in clinical research, will help to minimize bias, promote concordant care, and assist with developing sustainable solutions. The diversification of participation in neuro-oncology clinical trials is imperative. The lack of diversity in clinical trials can contribute to improper generalizability of treatment efficacy, resulting in potentially harmful practices. Equitable access and inclusion of URM brain tumor patients will not only enhance research discoveries but will also result in improved patient care for all cancer patients.